Refractometry With a Tailored Sensitivity Based on a Single-Mode-Capillary-Single-Mode Fiber Structure - Xiaobei Zhang; Haiyang Shao; Yong Yang; Haiyang Pan; Fufei Pang; Tingyun Wang (IEEE Photonics Journal, 2017)
We demonstrate a simple structure for the refractive index sensing by splicing a segment of capillary with two segments of single-mode fibers (SMFs). By selecting appropriate splicing parameters, two mode coupling regions can be formed with tapered air-cavities on both sides of the capillary. This simple structure allows us the light propagation in the capillary with a ring mode distribution, while the high-order mode distributed in the capillary will be affected by the surrounding environment. With the inner diameter of the capillary increases, there is an enhancement of interaction between ring modes and the surrounding environment. Therefore, we can realize a tailored sensitivity based on the inner capillary diameter. Maximum refractive index sensitivities of 789, 1196, and 1684 nm/RIU can be obtained in the refractive index range from 1.3360 to 1.4365 when the inner diameter is 5, 15, and 25 μm, respectively. The distinguishing feature of such a capillary-based fiber sensor is that it can be used for the refractometry with a tailored high sensitivity through choosing the inner capillary diameter.